O tráfico de andaluzes para o café: cafeicultores paulistas no negócio de atração e transporte de imigrantes (1886-1918) - Alegre, Silvia Elena (2014)
This research deals with the Andalusian immigrants, attracted by the offer of tickets financed by the São Paulo government, aimed at working in the coffee plantations in the countryside of the São Paulo state. Immigration performed by free tickets was highly dependent on the recruitment activity, which was prohibited by the Spanish law. When, in 1910, the Spanish government banned subsidized emigration to Brazil, the boarding of workers continued to be carried out from the English port of Gibraltar, outside its jurisdiction. This paper seeks to show how the São Paulo coffee growers, committed to keeping active flow of labor to the plantations in sufficient quantity to provide a surplus that would allow a favorable negotiation to their interests, were directly involved with the agencies responsible for the attraction and overseas transportation of immigrants even when this activity involved breaking the law. The participation of the coffee growers elite and their representatives in the São Paulo state government in the trafficking of immigrants to the farms reveals the relationship of the Brazilian ruling classes with the law, a relationship marked by arbitrariness and wide maneuvering margin. The analysis of the case here presented, researched from crossing the Spanish and Brazilian documentation, is an attempt to understand the paradoxical aspects of the modernization of Brazil ingrained with remains from the colonial past